The Political Salience of Animal Protection in the Republic of Ireland (2011–2020): What Do Irish Political Parties Pledge on Animal Welfare and Wildlife Conservation? - Annick Hus; Steven P. McCulloch (Animals)
Ireland is the largest beef trader and a major dairy exporter within the European Union. Horse racing holds significant cultural value, while greyhound racing is economically important at the regional level. As public concern about farm animal welfare rises and biodiversity loss intensifies, this research examines the political salience of animal protection in Ireland across the 2011, 2016, and 2020 general elections. Political salience measures the degree of public concern about political issues, with party manifestos serving as indicators of this concern. Using both quantitative and qualitative methods, this study analysed 364 statements on animal protection from Fianna Fáil, Fine Gael, the Green Party, the Labour Party, and Sinn Féin. The results show a significant increase in the frequency and positivity of animal protection statements over the course of the election period, with a shift in the attitudes of Fianna Fáil and Fine Gael. The Green Party has consistently promoted progressive animal protection policies. Key issues such as farmed animal welfare, wildlife and biodiversity, and horse and greyhound racing have gained prominence in party manifestos, also reflecting economic influences. Despite this growing focus, critical issues such as the puppy trade and certain aspects of farmed animal welfare remain underrepresented. This research provides the first comprehensive academic analysis of animal protection policy in political party manifestos in the Republic of Ireland.